A Retrospective Study Of Morbidity In Captive Columbiformes Housed In Bristol Zoo Gardens And Wild Place Project, United Kingdom From 2000 – 2017 - Irhamna Putri Rahmawati (The International Journal of Tropical Veterinary and Biomedical Research, 2018)
Medical records from 860 pigeons and doves of 24 species housed in Bristol Zoo Gardens and Wild Place Project, United Kingdom, from 2000 to 2017 were reviewed to determine the causes of morbidity in captive columbiformes. Accounted 205 cases (51.25%), infectious disease was found as the primary cause of morbidity, followed by 133 cases of trauma (33.25%), 51 (8.9%) cases of non-infectious disease, and 8 (2%) cases of husbandry-related problem. The main cause of infectious disease was parasite infection with 35% over 31% of bacterial, 26% of undetermined etiology and 9% of fungal infection. More specific, nematodiasis was the most frequent parasitic disease found, presented in 49 (69%) cases and followed by 10 (14%) trichomoniasis of all parasite infection. Meanwhile, chlamydiosis was a leading cause of bacterial infection with 22 (35%) cases recorded of over 63 bacterial infections. These results highlight the importance of preventative medicine implementation in captivity which aims to detect the disease earlier hence reducing the worsening physical condition and minimising the risk of both zoonotic and non-zoonotic disease transmissions. In addition, these findings contribute to the limited information available regarding the captive columbiformes morbidity